Efektivitas Penerapan Metode Qatar Foundation dalam Penguasaan Kefasihan dan Kelancaran Berbicara Bahasa Arab - Siti Farhani; Restu Budiansyah Rizki (Al-Mazaya: Jurnal Pendidikan Bahasa Arab, 2025)
Despite a solid understanding of linguistic structures, many students continue to struggle withspeaking Arabic fluently and confidently. The Qatar Foundation method emerges as a strategic response tothis issue by fostering fluency and self-assurance through interactive, communication-based techniques.This research investigates how the method is implemented to strengthen Arabic speaking proficiency andevaluates its effectiveness within the Best Speaker class of the Natiq Arabiyah program in Pare, Kediri.Employing a quantitative research design with eight participants, data were gathered via interviews,observation, testing, and documentation. Analysis was conducted using a one-sample t-test. The resultsshow that applying the Qatar Foundation method strategically contributes to significant improvements instudents' speaking abilities. This approach aligns with the Natiq curriculum while promoting criticalthinking. Its effectiveness is validated through five performance indicators: fluency, accuracy, tajweed,movement, and expressive delivery—with a t-test result (5.170 > 2.306) that confirms its impact.Accordingly, the Qatar Foundation method is recognized as a highly effective approach for enhancing Arabicspeaking skills in this instructional context